To simplify the expression \(8a - 2a\), you can combine the like terms:
\[ 8a - 2a = (8 - 2)a = 6a \]
So, the simplified expression is \(6a\).
11 answers
To simplify the expression \(8a - 2a\), you can combine the like terms:
\[ 8a - 2a = (8 - 2)a = 6a \]
So, the simplified expression is \(6a\).
To simplify the expression \(12e - 5f - 7e + 3f\), you can combine like terms.
First, combine the terms with \(e\):
\[ 12e - 7e = (12 - 7)e = 5e \]
Next, combine the terms with \(f\):
\[ -5f + 3f = (-5 + 3)f = -2f \]
Now, putting it all together, the simplified expression is:
\[ 5e - 2f \]
The simplified expression for \(12e - 5f - 7e + 3f\) is:
\[ 5e - 2f \]
To simplify the expression \(9x + 3y - 6 - 5x + 4y - 3\), we can combine like terms.
Combine the \(x\) terms: \[ 9x - 5x = (9 - 5)x = 4x \]
Combine the \(y\) terms: \[ 3y + 4y = (3 + 4)y = 7y \]
Combine the constant terms: \[ -6 - 3 = -9 \]
Putting it all together, the simplified expression is:
\[ 4x + 7y - 9 \]
To simplify the expression \(911z - 411z\), you can combine the like terms:
\[ 911z - 411z = (911 - 411)z = 500z \]
So, the simplified expression is \(500z\).
The simplified expression for \(911z - 411z\) is:
\[ 500z \]